Attainment of Programme Outcomes through Course Outcomes in Outcome Based Education:A Case Study - Balasubramani, R.; Chiplunkar, Niranjan N. (Journal of Engineering Education Transformations, 2017)
In the new Outcome Based Education model as prescribed by National Board of Accreditation (NBA), one of the most important criteria is the Attainment of Programme Outcomes (POs). The Programme Outcomes are specific rather than narrower statements that describe what students are expected to know and be able to do upon the graduation. These relate to the skills, knowledge, and behavior that students acquire in their matriculation through the programme. The Programme Outcomes can be attained through the attainment of Course Outcomes of the courses pertaining to that programme. In this paper a sample course viz. Building Enterprise Applications has been selected to demonstrate the process involved in the attainment of Course Outcomes. The contribution of Course Outcomes to Programme Outcomes is also demonstrated.